Solutions for fuzzy matrix games - Cevikel, Adem C.; Ahlatcioglu, Mehmet (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
In this paper, we deal with two-person zero-sum games with fuzzy payoffs and fuzzy goals. We have presented two models for studying two-person zero-sum matrix games with fuzzy payoffs and fuzzy goals. We assume that each player has a fuzzy goal for each of the payoffs. We obtained that the fuzzy relation approach and the max-min solution are equivalent. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Fuzzy goal; Fuzzy payoff matrix; Fuzzy relation; Fuzzy quantity; Nonlinear programming problem; Max-min solution; Relaxation procedure; Two-person zero-sum games; MULTIOBJECTIVE BIMATRIX GAMES; EQUILIBRIUM SOLUTIONS; DUALITY; GOALS; PAYOFFS; Mathematics